Antropologia como educação: um diálogo sobre experiências de ensino da antropologia em cursos de formação de professores e seus desafios - Ceres Karam Brum (Universidade do Vale do Rio dos Sinos (UNISINOS), 2018)
Inspired by the Tim Ingold reflexions on knowledge systems (2000), about Anthropology and Education (2008a, 2008b) and the way for the maze and the labyrinth (2015), this work intends to dialogue about the place of anthropology in teacher education in Brazil. Our goal is to propose a discussion about the characteristics of the processes of teaching and learning occurring in undergraduate courses for teachers, dialoguing with the limitations imposed by the Hermetic conception of education translated in the maze metaphor also proposed by Ingold (2015). The analysis will take place from the experiences of the authors in these formative contexts and research carried out under Anthropology of Education in Brazil. Jesus, based on his teacher training, argues about the need to think the teaching of anthropology from a reflection on knowledge systems. Brum reflects on the opening of multiple educational pathways provided by the anthropology of education at the Federal University of Santa Maria.